GAMBARAN KARAKTERISTIK DAN HASIL PELAKSANAAN DETEKSI DINI KANKER SERVIKS DENGAN METODE IVA (INSPEKSI VISUAL ASAM ASETAT) PADA IBU PASANGAN USIA SUBUR DI PUSKESMAS PADANG PASIR - Lola Fizria, Dian Febrida Sari (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
WHO states as many as 80% of deaths due to cervical cancer cases occur in developingcountries, at least 231,000 women worldwide died from cervical cancer (cervix)in 2015. Thepurpose of this study was to determine the Characteristic And Implementation Results of EarlyDetection of Cervical Cancer with Inspection of Visual Acetat (IVA) Methods In Infertile AgeMother at Puskesmas Padang Pasir in 2016. This research type is descriptive by usingsecondary data. This research was conducted at Padang Pasir Puskesmas with data collectionon July 15, 2017. The research population was all mothers of fertile couples who performedthe results of IVA examination at Padang Pasir Puskesmas in 2016, ie as many as 333 people,sampling the study using total sampling technique. The type of data in this study is secondarydata with aids that is the format of data collection. Data processing technique is done byediting, coding, entry, tabulating and cleaning then the data is analyzed univariat. The resultsof the study were 211 (63.4%) of the respondents were at risk, 292 (87.7%) of respondentswere not at risk, 304 (91.3%) of respondents were at risk, 176 (52.9% %) Of respondents hadrisk parity, 324 (97.3%) of respondents of higher education, 322 (96.7%) of respondents didnot work, 293 (88.0%) most IVA test results (-).Keywords : Early detection, IVA Method